MEDIA PUZZLE PIZZA SEBAGAI ALAT BANTU PEMBELAJARAN PECAHAN BERPENYEBUT TIDAK SAMA DI SEKOLAH DASAR - Zulfanur Fayuda; Angelita Safitrianingrum; Erin Putri Rindiani; Bima Darma Wijaya; Rozi Firnas Rahman; Azamul Fadhly Noor Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Difficulties in understanding fractions with unlike denominators remain a common problem in elementary mathematics learning. These difficulties are often caused by abstract teaching approaches and limited use of concrete learning media. This study aims to analyze the effectiveness of pizza puzzle media as a learning aid in teaching fractions with unlike denominators in elementary schools. The research employed a literature review method by systematically analyzing national journal articles published within the last ten years. Data were collected from reputable databases such as Google Scholar, SINTA, and Garuda using keywords related to puzzle media, fraction learning, and elementary mathematics education. The results of the literature analysis indicate that pizza puzzle media effectively improves students’ conceptual understanding of fractions, reduces misconceptions in comparing and adding fractions with different denominators, and increases student learning activity and motivation. The visual and manipulative characteristics of pizza puzzle media help students understand fractions as parts of a whole and support meaningful learning experiences. Therefore, pizza puzzle media can be considered an effective and relevant instructional aid for teaching fractions with unlike denominators in elementary schools. Keywords: Pizza Puzzle Media, Fractions, Unlike Denominators, Elementary Mathematics